Prevalence and risk factors of sarcopenia in patients with multiple system atrophy - FU Jin, LIU Yanping, WANG Han, WANG Rui, YU Kang (Jichu yixue yu linchuang, 2024)
Objective To find the prevalence of sarcopenia in patients with multiple system atrophy(MSA)and to explore the muscle related risk factors that affect the ability if living and exercise of patients. Methods Through a cross-sectional study, patients with Parkinson's disease(PD) and movement disorders who visited the multidisciplinary outpatient clinic of Peking Union Medical College Hospital from October 2022 to December 2023 were included. Their demographic data and disease duration were collected. The modified Barthel Index (simplified Chinese version) was applied to evaluate the participants' living ability. The severity of movement disorders and non-motor symptoms were evaluated by the Unified PD rating scale. The body composition, grip strength, SARC-F score were used to evaluate the muscle condition of patients and the diagnosis of sarcopenia and pre sarcopenia were made according to EWGSOP2. Results Among 44 patients included in this study, 8(18.8%) were diagnosed with sarcopenia, 17(38.6%) were pre-sarcopenia and 19(43.2) had normal muscle condition. There were significant differences in disease-related clinical characteristics among the three groups. MSA patients were characterized by older age(P＜0.01).They had lower BMI (P＜0.01), and worse disease symptom score (P＜0.01), SARC-F score(P＜0.05), and activity score (P＜0.01), significantly reduced fat removal weight (P＜0.01) and phase angle (P＜0.05). Regression analysis showed that SARC-F score, grip strength, limb skeletal muscle index and fat free weight were all independent risk factors affecting the ability of living and exercise of MSA patients. Conclusions The preval-ence of MSA sarcopenia is higher and sarcopenia is closely associated with more severe clinical illness and lower living ability. It is an independent risk factor for increased living ability score and motor function score.